2015
DOI: 10.1039/c5ra12275a
|View full text |Cite
|
Sign up to set email alerts
|

In situ growth of nickel selenide nanowire arrays on nickel foil for methanol electro-oxidation in alkaline media

Abstract: NiSe nanowire arrays solvothermally grown on nickel foil behave as an efficient 3D anode for electro-catalytic oxidation of methanol in alkaline media with strong durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Among the several alternative materials proposed to replace noble metals as MOR catalysts, Ni offers the highest cost‐effectiveness. A plethora of Ni [12–14] and Ni‐based catalysts, including oxides/hydroxides, [15–17] metal alloys, [18–23] phosphides, [24] chalcogenides, [25] and nitrides, [26] have been developed and tested toward MOR. Surprisingly, the nickel carbide, which a priori offers suitable properties as electrocatalysts, for example, stability, electrical conductivity and element abundance, has not been tested toward MOR.…”
Section: Figurementioning
confidence: 99%
“…Among the several alternative materials proposed to replace noble metals as MOR catalysts, Ni offers the highest cost‐effectiveness. A plethora of Ni [12–14] and Ni‐based catalysts, including oxides/hydroxides, [15–17] metal alloys, [18–23] phosphides, [24] chalcogenides, [25] and nitrides, [26] have been developed and tested toward MOR. Surprisingly, the nickel carbide, which a priori offers suitable properties as electrocatalysts, for example, stability, electrical conductivity and element abundance, has not been tested toward MOR.…”
Section: Figurementioning
confidence: 99%
“…4) Scrupulously building transition‐metal oxides or hydroxides based multi‐stage nanoarray architecture on foams. Notably other than these metal oxide or hydroxide nanoarrays, transition‐metal phosphide and chalcogenide nanoarrays such as CoP nanowire arrays on carbon cloth and NiSe nanowire arrays on Ni foil have also been reported that they could efficiently catalyze the MOR. Moreover, recent work done by Li and co‐workers shows that coupling CoP with Pd to build 3 D Copepod hybrid nanosheet arrays on carbon fiber cloth could serve as an integrated electrode to catalyze the electro‐oxidation of ethanol in a basic medium with ultra‐high catalytic activity and excellent stability .…”
Section: Direct Methanol Fuel Cellsmentioning
confidence: 99%
“…The resulting compound showed much higher electrocatalytic activity for methanol oxidation than pure Ni salen A due to an identified synergetic effect [11,12]. Peng et al developed a simple solvothermal method for in situ growth of Ni-Se nanowire arrays on Ni foil [13], then through a hydrothermal process/annealing treatment first synthesized the hierarchical nickel oxide nanosheet@nanowire arrays on nickel foam (NiO NS@NW/NF). Notably, these catalysts all exhibited high electrocatalytic activity and stability [14].…”
Section: Introductionmentioning
confidence: 99%